Differences Between Exergaming Rehabilitation and Conventional Physiotherapy on Quality of Life in Parkinson's Disease: A Systematic Review and Meta-Analysis - Elena, Papamichael; Demetris, Solou; Christina, Michailidou; Marios, Papamichail (Frontiers in Neurology, 2021)
Parkinson's disease (PD) is a neurodegenerative condition with both motor and non-motor symptoms affecting the quality of life (QoL) of older adults. Exergaming rehabilitation allows the interaction of the subject with digital games through the implementation of repetitive functional activities. Conventional physiotherapy uses patient-centered programs that include a variety of active exercises. The aim of this review was to look into the effectiveness of exergaming rehabilitation on the QoL of people with PD and compare it with conventional physiotherapy. Five electronic databases were searched for eligible studies until February 2021. For the statistical analysis, the mean, standard deviation, and 95% confidence interval were used to calculate effect sizes between groups. To determine heterogeneity, statistical index I2 was used. A total of 548 participants were included in 14 studies. Exergaming rehabilitation related with improved QoL (p = 0.687, 95% CI: −1.682 to −0.734), balance (p = 0.039, 95% CI: 0.364–13.689), (p = 0.018, 95% CI: 0.446–4.830), and gait (p = 0.005, 95% CI: 0.351–1.924). No significant difference was found between groups regarding the Unified Parkinson's Disease Rating Scale (p = 0.196, 95% CI: −5.970 to 1.225) and for the Timed Up and Go Test (p = 0.12, 95% CI: 0.446–4.830). Exergames as a rehabilitation method can be used to provide alternative interactive intervention with positive results for QoL in people with PD. Further investigation is needed to assess the effect on mental health in this population group.